Redesigning the identities of teachers and leaders: A framework for studying new professionalism and educator resistance - Anderson, Gary; Cohen, Michael (Education Policy Analysis Archives, 2015)
Neoliberal reforms of public education do more than shape policy and curriculum; they also influence educators’ understanding of themselves as professionals, driving at the very core of what it means to be a teacher or leader. This article explores the effects of Neoliberal policies and New Public Management pracitces on teachers and principals and the ways they result in a “new professionalism.” The authors provide a framework for studying how these new polices and practices might be resisted, as well as a description of characteristics of the new professional and what professionalism might look like if it were grounded in community and advocacy.